The Influence of Grit on Nurses’ Job Burnout Decrease in Depok Secondary Hospitals - Safariningsih, Ratna Tri Hari; Rizan, Mohamad; Handaru, Agung Wahyu (Interdisciplinary Social Studies, 2022)
One of the professions with a significant risk of burnout is nursing. As a result of constantly having to regulate their emotions when interacting with patients, nurses have a higher emotional threshold. Physical fatigue, a lack of job satisfaction, and subpar performance can all be caused by emotional exhaustion. Burnout was found to have a detrimental impact on nurse loyalty and service quality. The purpose of this research is to determine the role of grit in reducing job burnout among secondary hospital nurses in Depok, West Java Province, Indonesia. Cross-sectional design, a quantitative approach, was utilized in this study. The study's participants were all the medical staff members employed by three secondary hospitals in Depok City, West Java, Indonesia. This study included 150 nurses from three hospitals as samples. Simple linear regression analysis was used to analyze the data. The findings indicate that grit has a negative and significant impact on job burnout. With a R Square of 0.190, it is clear that other variables account for the remaining 89% of the job burnout variable, leaving only 19% to be explained by grit. Hospitals should analyze their nurses' workloads and create a work culture of mutual support. Nurses should set career goals and continue to learn new skills.